2006
DOI: 10.1590/s0100-204x2006000300016
|View full text |Cite
|
Sign up to set email alerts
|

Micromorfologia do solo e sua relação com atributos físicos e hídricos

Abstract: Resumo -O objetivo deste trabalho foi avaliar a relação entre atributos micromorfológicos e físicos de um Latossolo Vermelho eutroférrico, sob cultivo de cana-de-açúcar. As amostras de solo foram coletadas nos pontos de cruzamento de uma malha, com intervalos regulares de 10 m, perfazendo um total de 100 pontos, nos horizontes A1 e AB. Os altos valores da densidade do solo, microporosidade e resistência do solo à penetração, e os baixos valores da macroporosidade, porosidade total e condutividade hidráulica do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
35

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 15 publications
4
10
0
35
Order By: Relevance
“…Similar values were observed by Souza et al (2006) and Roque et al (2010) sugarcane. Penetration resistance only reached a level considered restrictive to root growth (>2 MPa) (Otto et al, 2011) in the plant row in the management NTC, indicating the soil physical degradation.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Similar values were observed by Souza et al (2006) and Roque et al (2010) sugarcane. Penetration resistance only reached a level considered restrictive to root growth (>2 MPa) (Otto et al, 2011) in the plant row in the management NTC, indicating the soil physical degradation.…”
Section: Resultssupporting
confidence: 88%
“…Research has shown the effect of compaction on the soil physical quality, increasing soil density and mechanical strength (Materechera, 2009;Cavalieri et al, 2011) and decreasing the pore volume, particularly of macropores (Streck et al, 2004;Souza et al, 2006;Braunack & McGarry, 2006). Soil compaction also affects the soil structure, changing the aggregate stability and modifying the particle arrangement (Tullberg et al, 2007;Roque et al, 2010;Vezzani & Mielniczuk, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The lowest value was obtained for texture (0 %) and the highest for PR 0.05 m (80 %). With exception of texture, with strong DD, and PR 0.05 m, with weak DD, the other properties had moderate DD, agreeing with various authors who also studied soil physical properties (Mercante et al, 2003;Silva et al, 2004;Grego & Vieira, 2005;Souza et al, 2006;Siqueira et al, 2008). Predominance of moderate spatial dependence and strong dependence indicate that absence of tilling does not necessarily affect the varibility of soil properties.…”
Section: Soil Physical Propertiessupporting
confidence: 88%
“…The CV value was highest for the surface layer to a depth of 0.05 m and was practically the same in the three subjacent layers (23.53, 24.99 and 23.32 %). Abreu et al (2003) and Souza et al (2006) reported similar behavior for the same depths. High CV values for PR had already been expected due to the wide variations of this variable and measurement errors that influence the value.…”
Section: Soil Physical Propertiesmentioning
confidence: 56%
“…In Brazil, the observations made by Souza et al (2006) from microscopic analysis of thin sections of a Latossolo Vermelho distroférrico (Oxisol) planted to citrus also reveal differences in pore space geometry as a result of changes caused by management. Therefore, the purpose of this study was to evaluate the influence of conventional agricultural management on the structure and microstructure of a Rhodic Hapludox in an experimental area planted to maize in the region of Campinas, SP, Brazil.…”
Section: Resumo: Alterações Morfológlcas E Micromorfológicas Na Estrumentioning
confidence: 99%